Pengembangan LKS Berbasis Kearifan Lokal di Malang Untuk Siswa Kelas IV SD - Arina Restian; Tyas Deviana; Yunia Nanda Eka Saputri (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This research aims to 1) develop a worksheet based on local wisdom in Malang for students in 4th grade, within subtheme 2: “The Beauty of My Country Cultural Diversity”, 2) test the effectiveness of the worksheet. This study uses ADDIE model, there are 5 stages namely analysis, design, development, implementation, evaluation. The instrument was validated by material expert, instructional materials expert, and linguists. Then the revised worksheet was tested on the subject as a trial to find out the attractiveness and effectiveness. The validation result from the material expert was 90.67% in valid criteria, from the teaching material expert was 73.33% in criteria, and from the linguists were 93.33% in valid criteria. The attractiveness results 91.71% from students in interesting criteria and 85.71% from teachers. The effectiveness test results obtained 94.28% in effective criteria.